Biometric authentication and image encryption for image security in cloud framework - Kakkad, Vishruti; Patel, Meshwa; Shah, Manan (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2019)
Cloud computing is a major blooming technology which has numerous applications in today’s market and is rightly so hyped. Images are a major part of today’s internet data traffic, especially due to widespread social media, and hence, its security is crucial. However, in the present scenario, the images in cloud are a major issue in terms of security. Since the user who has uploaded the image has no control over the security of images, the cloud provider has to ensure maximum security in terms of authentication and prevention from attacks. The main objective of this paper is to provide a method to enhance the safety of images on cloud. This paper presents an idea of securing images on cloud platform using biometric authentication. Different steps involved in biometric authentication and secure upload and access of images are explained, and integration of all the steps is done at the end as a case study which puts light on the whole process in which methods are best-regarding results and compatibility. The proposed algorithm in this paper presents the idea of authentication of images in two basic steps of image compression using standard discrete wavelet transform method followed by image encryption using the hybrid method of SHA and blowfish. This image is then stored into the database of cloud and accessed whenever the user requests it. A structured and comprehensive view of encryption methods, types of biometrics and to secure data as well as images is provided in this paper.